1993
DOI: 10.1165/ajrcmb/9.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in the Calcitonin Gene-related Peptide (CGRP) Content of Pulmonary Endocrine Cells Concomitant with Vascular Remodeling in the Hypoxic Rat

Abstract: Morphologic changes are reported to occur in rat lung vasculature after 3 days of hypoxia. We have previously shown that immunoreactivity for the vasodilator calcitonin gene-related peptide (CGRP) is increased in pulmonary endocrine cells by 7 days of hypoxia. Because these cells may be among the earliest mediators of the hypoxic response, we examined endocrine cell CGRP content in rat lung after 0, 2, 4, and 8 h and 1, 5, 10, 15, 20, 28, and 35 days of normobaric hypoxia, using optimal and supraoptimal diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The pulmonary endocrine cells, found scattered in the airway epithelium, are a major source of CGRP in rat lung [1]. They are known to respond to changes in oxygen tension [6,24,25], and suggested to contain increased levels of CGRP [7] from 4 h after exposure of rats to hypoxia [26], which is reinforced by the finding of increased CGRP concentration in lung homogenates [5]. This higher level of CGRP could represent a suppression of its release, which is supported by decreased levels of CGRP in plasma [5], and the reversal of hypoxic pulmonary vascular remodelling by administration of CGRP [27].…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary endocrine cells, found scattered in the airway epithelium, are a major source of CGRP in rat lung [1]. They are known to respond to changes in oxygen tension [6,24,25], and suggested to contain increased levels of CGRP [7] from 4 h after exposure of rats to hypoxia [26], which is reinforced by the finding of increased CGRP concentration in lung homogenates [5]. This higher level of CGRP could represent a suppression of its release, which is supported by decreased levels of CGRP in plasma [5], and the reversal of hypoxic pulmonary vascular remodelling by administration of CGRP [27].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, might the products released from the cells of the system ever contribute to pulmonary pathology? It has already been described how increased numbers of neuroendocrine cells parallel the activity of myofibroblasts in PPA, suggesting a role for GRP or other pulmonary peptides in its pathogenesis, a possibility given recent support by a study of CGRP-containing neuroendocrine cells during hypoxic pulmonary vascular remodelling in the rat (Roncalli et al, 1993). Experiments in animals have suggested that these pulmonary neuroendocrine cell products might stimulate fibrogenesis (Johnson et al, 1980;Sheppard et al, 1982) and others have proposed such a role in causing the fibrosis which accompanies or results from a variety of pulmonary diseases (Aguayo et al, 1990(Aguayo et al, , 1992Johnson and Georgieff, 1989).…”
Section: Causes and Consequences Of Changes In The Systemmentioning
confidence: 91%
“…Apparent proliferative changes have also been observed in hypoxic conditions of man and various Himalayan species of animals, and changes in the CGRP content of PNEC in experimental hypoxia in rats have been reported. Immunocytochemistry, electron microscopical and molecular biological techniques all point to an increase in the CGRP content of existing CGRP-containing cells in the airways of animals subjected to hypoxia for periods from 1 to 21 days (Roncalli et al, 1993;Springall et al, 1988) (see also below). The apparent increase in the number of CGRP-containing cells is only due to an increase in the peptide content (McBride et al, 1990) making more cells visible by immunocytochemical techniques.…”
Section: Peptides In Pnecmentioning
confidence: 99%